(untitled) (Sociologisk Forskning, 2023)
In this paper, energy communities are examined as an arena within which the possibilities for a just and democratically oriented climate transition are currently being enacted. More specifically, it explores how energy communities (ECs) in Sweden are taking shape against the background of the EU’s Clean Energy Package, wherein ECs have been identified as an important instrument for increased citizen participation and deepened democratization. With our theoretical basis in critical social research, we examine the Swedish landscape of energy communities as a discursive battlefield, where sociomaterial arrangements and actor interests are under formation. Special attention is paid to actors’ political drivers for engagement, the ideological motivations that are expressed, the transformative strategies that are put into play, and the alliances that are formed. We argue that this is of sociological importance to scrutinize how laudable ambitions and visions of a climate-neutral society are put into practice, so as to illuminate power relations that otherwise risk being made invisible. We find that Swedish energy communities are generally forced to relate to a dominant innovation-oriented discourse with a depoliticizing effect. At the same time, we note that a variety of other ways of enacting community energy abound, which reflect values that deviate from the dominant discourse.